Two-party cooperative blind signature based on SM2 - Xue BAI; Baodong QIN; Rui GUO; Dong ZHENG (网络与信息安全学报)
SM2, issued by China in 2010, is a public key cryptography standard based on elliptic curves.It has been widely used in finance, social security and other fields thanks to its advantages of improved signature efficiency, decreased storage space and computing complexity than RSA.With the popularization and application of SM2, the issues of its key security and data privacy are of great concern.The single-key mode inhibits the potential application in multi-user settings, and the leakage of the key will threaten the security of the entire cryptosystem due to the centralization.The problem of secure storage and reasonable utilization of keys needs to be solved urgently.In addition, the SM2 digital signature algorithm cannot guarantee the message privacy.Aiming at the issues of key security and data privacy of the signature algorithm, many researchers have proposed the idea of cooperative signature and blind signature for SM2.However, there isn’t SM2 collaborative blind signature scheme proposed.Then a two-party cooperative blind signing protocol based on SM2 was proposed in this paper, which allowed two parties to sign except the user.The signing process did not require recovering the complete private key, while not revealing the information of the partial private key and secret number.The key was stored separately to improve the security of the key, while the blind signature protected the privacy of the message.In terms of security, the protocol satisfied unforgeability and unlinkability.The protocol was implemented using C to demonstrate the efficiency of each participant’s local operation.In the honest model, the time cost of each entity in the cooperative signature phase was similar as that of executing a lightweight SM2 blind signature.Overall, the proposed protocol has certain advantages in terms of function and efficiency.